Study Group for Establishment of Diagnosis of Hereditary Gastrointestinal Tract Cancer Syndromes Based on a Next-Generation Sequencing Technology - Ishida, Hideyuki; Eguchi, Hidetaka; SGHGCS; Okazaki, Yasushi (JOURNAL OF FAMILIAL TUMORS, 2019)
Clinical features of the hereditary gastrointestinal cancer syndrome overlap each other to some extent, and thus it is sometimes difficult to provide a definite diagnosis solely based on the clinico-pathological factors and family cancer history. In order to solve this big-issue, we established a Study Group for Establishment of Diagnosis of Hereditary Gastrointestinal Tract Cancer Syndromes Based on a Next-Generation Sequencing Technology (SGHGCS) in 2013. We briefly summarize our research activities thus far in accordance with the related ones of domestic and international. In 2019, the era of cancer-genome medicine comes finally true here in Japan. Numbers of problems to be solved about this are assumed. A possible establishment of a collaborative relationship among various study groups relative to the familial cancer may provide a clue to cope with these important matters.